COMPLETE INTERSECTION CALABI-YAU MANIFOLDS - Candelas, P; Dale, A; Lutken, C; Schimmrigk, R (1988)
An investigation is made of a class of Calabi-Yau spaces for which the manifold may be represented as a complete intersection of polynomials in a product of projective spaces. There are at least a hundred topologically distinct manifolds in this class. All manifolds in this class have negative Euler numbers which lie in the range of -200 ≤ χ ≤0. © 1988.